Bagaimana Peran Tata Kelola Perusahaan Dalam Hubungan Antara Manajemen Laba Dan Risiko Idiosinkratik di Indonesia? - Amrie Firmansyah,; Nopriyanto Hady Suhanda (Jurnal Ekonomi, 2021)
This study aims to investigate the effect of accrual earnings management and real earnings management on idiosyncratic risk. In addition, this study also examines the role of corporate governance in the relationship between the two. This study uses a quantitative approach. Research data obtained from www.IDX.co.id and www.finance.yahoo.com in financial report data and company stock prices from 2012 to 2017 are listed on the Indonesia Stock Exchange. Based on purposive sampling, the total sample of this study amounted to 244 observations. Hypothesis testing is conducted by employing multiple linear regression analyses for panel data. This study suggests that real earnings management and accrual earnings management have a positive effect on idiosyncratic risk. This study also finds that corporate governance fails to weaken the relationship between earnings management and idiosyncratic risk. This study indicates that the Indonesia Financial Services Authority needs to coordinate with the Indonesian Institute of Accountants to reduce earnings management actions by companies listed on the Indonesia Stock Exchange.